Broadband Vibration-Isolating Metamaterial for MRI-Induced Vibrations - Arawade, Swapnil; Piechowicz, Janusz Piotr (Archives of Acoustics, 2026)
The magnetic resonance imaging (MRI) is an important diagnostic tool in medical field. The vibrations originated from the gradient coil of MRI system leads to loud operational noise. The study explores the numerical investigation of elastic metamaterial for attenuation of MRI induced vibrations that could radiate as sound at air-structure interface. The elastic metamaterials with embedded resonators can significantly attenuate the wave propagation by opening a local resonance bandgap. In this study the wave propagation properties of two models of elastic metamaterial are analysed. The dispersion diagrams are studied with parametric analysis investigating the influence of the different geometric features on the bandgap generation. The model the metamaterial was analysed with finite element analysis to investigate the wave attenuation performance. The frequency analysis of the multicellular model showed high transmission loss corresponding to the bandgaps in calculated dispersion diagrams. The results revealed that, the optimum model of the metamaterial showed overlap of 72.3 % with the vibration frequency range of the MRI scanner and the frequency analysis of the multicellular arrangement reported transmission loss up to 115.7 dB. These results demonstrate the potential of the such elastic metamaterial for targeted vibro-acoustic control and provide a framework for design of structures for wave attenuation in sensitive acoustic environments.